2019
DOI: 10.2174/1567205016666190321154618
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and CNS Inflammation Crosstalk: Implications for Alzheimer’s Disease

Abstract: After years of failed therapeutic attempts targeting beta-amyloid (Aβ) in AD, there is now increasing evidence suggesting that inflammation holds a pivotal role in AD pathogenesis and immune pathways can possibly comprise primary therapeutic targets. Inflammation is a key characteristic of numerous diseases including neurodegenerative disorders and thus not surprisingly suppression of inflammation frequently constitutes a major therapeutic strategy for a wide spectrum of disorders. Several brain-resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 202 publications
0
44
0
Order By: Relevance
“…In the present study we only observed that um-PEA treatment failed to modulate the increased plasma TNF-α levels in 3×Tg-AD mice. However, it cannot be ruled out that the compound could reduce other markers of systemic inflammation, thus modulating the systemic and CNS inflammation crosstalk [61].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we only observed that um-PEA treatment failed to modulate the increased plasma TNF-α levels in 3×Tg-AD mice. However, it cannot be ruled out that the compound could reduce other markers of systemic inflammation, thus modulating the systemic and CNS inflammation crosstalk [61].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of microbial functions revealed the increased risks of immune systemic diseases and neurodegenerative diseases in CPE patients, and that neuroinflammation probably played a key role in the pathology of CPE (34). The elevated risk of immune system diseases was mainly attributed to the higher proportion of Akkermnsia in CPE patients.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of systemic TNFα can cross the blood-brain barrier (BBB), stimulating the microglia to secrete more TNFα as well as other proinflammatory factors and thus creating persistent and self-generated neuroinflammation [15]. Metabolic diseases such as obesity, hypertension, dyslipidemia, diabetes, and insulin resistance are associated with chronic systemic inflammation and a higher risk of developing neurodegenerative diseases such as Alzheimer's disease and PD [17][18][19][20][21][22][23]. Due to the importance of peripheral inflammatory processes in PD development [24][25][26], it is relevant to investigate more thoroughly the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%